THE DIFFERENT INFLUENT OF THE MODEL OF INQUIRI AND DISCOVERY LEARNING TOWARD THE OUTCOME OF STUDENT LEARNING - Desiani, Badriah (International Journal of Elementary Education, 2017)
This research aimed to find out the different learning outcome using inquiry and discovery learning model in 5th grade at Sidomukti sub-district. The subject of this research was 5th grade students at SDN Dukuh 02 as the control group and 5th grade students at SDN Mangun sari 01as experimental group. Independent variable consisted of inquiry and discovery learning model with dependent variable as the learning outcome. Data collection was conducted by using test. The technique analysis of the research result used descriptive statistic technique of Independent Sample T-test. Based on Independent Sample T-Test which was conducted in posttest score of control group and experimental group, it resulted significance/probability of 0,038<0,05, so that H0 was ignored and Ha was accepted it meant that there was different average between experimental and control group. The different which was significance were in two research samples, which the average score in implementing inquiry learning model was 79,75, whereas the score of discovery learning model is 75.00. it meant that there were significance differences from the learning outcome of the students who used inquiry learning model and the students who used discovery learning model with the 8 theme of Ecosystem.